Evaluation of Self-Compassion Focused Group Treatment for Co-Occurring PTSD and Substance Use in Veterans with Posttraumatic Guilt: A Case Study. Issue 4 (1st October 2020) - Eaton, Erica; Capone, Christy; Shea, M. Tracie; Cameron, Amy
ABSTRACT: Co-occurring posttraumatic stress disorder (PTSD) and substance use disorders (SUD) following combat exposure affects a significant proportion of military veterans. Guilt and shame are common to PTSD-SUD, suggesting a possible role as a mechanism underlying both disorders. Cultivating self-compassion (SC) among veterans is a logical approach to treating guilt and shame. The purpose of this article is threefold: (a) present scientific theories of SC in the veteran population with emphasis on PTSD, substance use, and guilt and shame; (b) present a case study that highlights how self-compassion-focused treatment (SCFT) can be utilized in a group format with veterans with PTSD-SUD and posttraumatic guilt; and (c) discuss implications of our findings for refining SCFT within a group intervention setting among this population and for future research.